Religion and culture : revisiting a close relative - Beyers, Jaco (Hervormde teologiese studies, 2017)
Religion and culture always exist in a close relation. Together with aesthetics and ethics, religion constitutes culture. As ethnicity becomes part of the related concepts, the relation with religion needs explanation. This article wants to emphasise that when studying religion, a study of culture is necessary. This statement is argued from three positions: (1) cultural migrations occurring worldwide, (2) religion as cultural identity marker causing the borders between culture and religion to blur and (3) the location of religion within culture causing religion to act as custodian of culture. This results in a situation where any signs of animosity towards culture are interpreted as opposition towards religion. All three arguments necessitate studying ethnicity when studying religion.